2015
DOI: 10.14740/jocmr2158w
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hyperbilirubinemia in a Turkish Cohort: Association of Vitamin B12

Abstract: BackgroundDeficiency of vitamin B12 (VitB12) causes failure of erytrocyte maturation leading to cell lysis. Red blood cell lysis causes excess heme production that ends with hyperbilirubinemia. In this study, we aimed to evaluate the role of VitB12 in neonatal hyperbilirubinemia (NNH) with prolonged jaundice and to compare patients with control group who did not develop hyperbilirubinemia.MethodsA total of 20 patients (M/F = 13/7) with jaundice and 20 healthy controls (M/F = 11/9) were included in the study.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Our result is in agreement with that of Eroglu et al [3] who found that the mean vitB12 level in patients was 119.9 ± 43.9 ng/L (42.35 -178 ng/L) while in controls was 286.17 ± 97.43 ng/L (207.90 -624.10 ng/L). They also stated that low vitB12 level has been observed as a risk factor in neonatal hyperbilirubinemia.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our result is in agreement with that of Eroglu et al [3] who found that the mean vitB12 level in patients was 119.9 ± 43.9 ng/L (42.35 -178 ng/L) while in controls was 286.17 ± 97.43 ng/L (207.90 -624.10 ng/L). They also stated that low vitB12 level has been observed as a risk factor in neonatal hyperbilirubinemia.…”
Section: Discussionsupporting
confidence: 94%
“…There is an evidence of increased vitB12 absorption during pregnancy, with the newly absorbed vitB12 being more important to placental transport than maternal liver stores. So that, lack of vitB12 rich diet of the mother may cause vitB12deficiency in newborn [3]. So, it is recommended that vitB12 supplement is necessary to avoid both neonatal vitB12 deficiency and hyperbilirubinemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that ineffective erythropoiesis may cause immature erythrocyte formation increasing hemolysis and indirect hyperbilirubinemia. 10 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, Dasari S et al 11 reported a patient aged 41 with hyperbilirubinemia who was diagnosed with vitamin B12 deficiency and his hyperbilirubinemia was eliminated following vitamin B12 treatment. In addition, Eroglu N et al 10 compared 20 cases with indirect hyperbilirubinemia of above greater than 5 mg/dL with 20 cases whose indirect bilirubin was below 5 mg/dL and found significant serum vitamin B12 deficiency in the former group. This is the only case control study identified in the literature.…”
Section: Discussionmentioning
confidence: 99%